"Whatever happened to our great gay imaginations?": The invention of safe sex and the visceral imagination. Issue 1 (2nd January 2021) - Mitchell, Ryan
ABSTRACT: This essay develops a theory of the visceral imagination by analyzing the first safe sex manual written in the age of AIDS— How to Have Sex in an Epidemic: One Approach . At the time of the manual's publication in 1983, no one knew for certain what caused AIDS. Drawing on the transmission pathways of common sexually transmitted infections and through thick descriptions of the contact between bodily fluids and internal membranes, the manual's authors, Michael Callen and Richard Berkowitz, constructed a comprehensive, customizable AIDS prevention framework. In this essay, I argue that these descriptions stabilized the controversies surrounding AIDS transmission by activating what I call the visceral imagination. The visceral imagination supports speculative, non-technical arguments about health with localized, vivid portrayals of the body, its orifices, and its fluids. Analysis of this case study illustrates that the visceral imagination can resist universalizing, curative approaches to biomedical intervention by inviting non-experts to negotiate risk against personalized assessments of bodily permeability. More broadly, a theory of the visceral imagination productively extends recent rhetorical interests in viscerality by illuminating embodied, imaginative practices that queer, grassroots, and other subjugated rhetors might use to resist the homogenizing effects of dominant, normative health discourses.